Love, attention and teaching: Dostoevsky's The Brothers Karamazov. Issue 1 (1st January 2018) - Roberts, Peter
ABSTRACT: Fyodor Dostoevsky's final novel, The Brothers Karamazov, is one of the most influential works of the nineteenth century. To date, however, the potential value of the book for educationists has been largely ignored. This article addresses a key pedagogical theme in The Brothers Karamazov, namely, the notion that 'love is a teacher'. Love as Dostoevsky understands it is active and difficult; it focuses not on the abstract idea of loving humankind but on the messy particulars of everyday life. Active love, it will be argued, has much in common with Iris Murdoch's concept of attention. The first part of the article examines several passages in The Brothers Karamazov that address the theme of active love. The second section analyses these examples from the text in the light of Murdoch's ideas and explores some of their broader educational implications.